2004
DOI: 10.4161/cbt.3.7.914
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a transcriptional profile associated with in vitro invasion in non-small cell lung cancer cell lines

Abstract: Although much has been learned about basic mechanisms of cell invasion, the genes whose expression is required for this process by malignant cell lines have remained obscure. We assessed invasion through Matrigel using EGF as a chemoattractant and gene expression profiles using oligonucleotide microarrays for 22 non-small cell lung cancer cell lines. The expression of 22 genes were significantly correlated (p < 0.001) with the measured invasion index. Cluster analysis demonstrated that gene expression profiles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…On the other hand wild-type PAI-1 increased cell motility in chemotaxic assays for human MDA-MB-435 breast carcinoma cells, while a non-protease inhibitory P14 (T333R) PAI-1 mutant did not [99]. Interestingly, in a microarray analysis of 22 non-small cell lung cancer cell lines, 16 genes were positively and 7 negatively associated with invasiveness: the gene with the highest positive association with invasion was the protease inhibitor PAI-1 [101], further strengthening the notion that PAI-1 effects on invasion are not mediated by modulating mere proteolytic activities. In a cutaneous healing model (epidermal monolayer scraping), injury site closure was inhibited by anti-sense down-regulation of PAI-1 synthesis (by 80-85%), or addition of PAI-1 neutralizing antibodies; these data strongly indicate that PAI-1 was required for efficient long-term planar motility of keratinocytes.…”
Section: Pai-1 and Migration/motilitymentioning
confidence: 94%
“…On the other hand wild-type PAI-1 increased cell motility in chemotaxic assays for human MDA-MB-435 breast carcinoma cells, while a non-protease inhibitory P14 (T333R) PAI-1 mutant did not [99]. Interestingly, in a microarray analysis of 22 non-small cell lung cancer cell lines, 16 genes were positively and 7 negatively associated with invasiveness: the gene with the highest positive association with invasion was the protease inhibitor PAI-1 [101], further strengthening the notion that PAI-1 effects on invasion are not mediated by modulating mere proteolytic activities. In a cutaneous healing model (epidermal monolayer scraping), injury site closure was inhibited by anti-sense down-regulation of PAI-1 synthesis (by 80-85%), or addition of PAI-1 neutralizing antibodies; these data strongly indicate that PAI-1 was required for efficient long-term planar motility of keratinocytes.…”
Section: Pai-1 and Migration/motilitymentioning
confidence: 94%
“…H661 did not have any significant expression of c-Met. Next, we examined the level of c-Met gene expression using the Affymetrix HG-U133A gene chip expression data obtained on the cell lines as reported previously (25). The c-Met gene expression for the H1993 cells was assessed using microarray data from the Affymetrix HG-U95Av2 gene chip.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously reported that Slug promotes tumor invasion and acts as an independent prognostic marker in lung adenocarcinoma (Shih et al, 2005). Another TGF-b upregulated gene, PAI-1 (SERPINE1), which is involved in the extracellular matrix remodeling, cell migration and tumor angiogenesis (Stefansson et al, 2003;Providence and Higgins, 2004;Binder and Mihaly, 2008), is also an independent predictor of cancer relapse and poor survival in patients with breast, lung, ovarian and oral squamous cell carcinoma (Kuhn et al, 1999;Foekens et al, 2000;Hundsdorfer et al, 2004;Lader et al, 2004;Werle et al, 2004). MMP-2 and MMP-9 have also been reported to promote tumor invasion and metastasis and act as prognostic factors in non-small cell lung cancer Figure 6 SCUBE3 is cleaved by purified recombinant MMP-2 and MMP-9 in vitro.…”
Section: Scube3 Regulates Emt Via Tgf-b Receptor Signaling Y-y Wu Et Almentioning
confidence: 99%